In‐Situ Study of Crystallization Behavior of a Mold Flux Using Single and Double Hot Thermocouple Technique. Issue 6 (9th February 2015) - Yang, Jian; Cui, Yaru; Wang, Lin; Sasaki, Yasushi; Zhang, Jianqiang; Ostrovski, Oleg; Kashiwaya, Yoshiaki; Yu, Aibing
<x xml:space="preserve">Abstract</x> In this study, crystallization behavior of an industrial mold flux was investigated using both single hot thermocouple technique (SHTT) and double hot thermocouple technique (DHTT). Continuous cooling transformation (CCT) and time‐temperature transformation (TTT) diagrams were constructed using SHTT. The critical cooling rate in continuous cooling process was determined as 7 °C s−1 above which a glassy phase was formed. The TTT diagram showed two noses at approximately 1000 and 1075 °C. Phase identification carried out using X‐ray diffraction (XRD) revealed that dicalcium silicate (Ca2SiO4) was the major phase at both 950 and 1100 °C, together with minor precipitates of Na2CaSi3O8 and Ca2MgSi2O7 whose concentrations were relatively higher at 950 °C. Cuspidine (Ca4Si2O7F2) was also identified by XRD at 950 °C. Crystallization kinetics was analyzed using Johnson–Mehl–Avrami–Kolmogorov equation. DHTT was used to simulate the temperature gradient between copper mold and strand in the continuous casting mold. Glassy phase was formed quickly near the cold side when it was quenched from 1500 to 800 °C. Crystals started to precipitate in the glassy region after 48 s. Then major part of the glassy region was gradually transformed to crystalline phase and the crystals subsequently grew to the liquid region. A steady three‐layer state was reached after 360 s.